Effect of nano-hydroxyapatite with biomimetic analogues on the characteristics of partially demineralised dentin: An in-vitro study - Sharanya Nambiar; Mohini Kumari; Sylvia Mathew; Swaroop Hegde; Poornima Ramesh; Nithin Shetty (Wolters Kluwer Medknow Publications, 2021)
Background: Research on dentin remineralisation protocols in particular 'biomimetic remineralisation' has gained huge momentum. Aim of this study was to evaluate if biomimetic analogs, incorporated in n-HAp, as an experimental formulation could aid in remineralization of artiﬁcial caries-like dentin and have anti-microbial effect on cariogenic bacteria, S mutans. Materials and Methodology: An experimental paste was formulated using nano-hydroxyapatite (nHAp) with Non-Collagenous Protein analogs- polyacrylic acid (PAA), sodium tri-poly phosphate (STPP) with Simulated Body Fluid. Partially demineralised dentin specimens were divided into three groups (n=10) based on the remineralisation treatment as, Group A- n-HAp paste, Group B- n-HAp and NCP analogues and Group C (Control) - no treatment. At the end of the experimental period, the specimens were assessed using SEM-EDS analysis and Vickers microhardness testing. Further, the antimicrobial efficacy of the paste was assessed. Statistical Analysis: The results were statistically analyzed using ANOVA with post-hoc Bonferroni test. Results: Dentin specimens treated with the experimental paste revealed greater tubular occlusion, with intra tubular deposits and increased mineral content. Specimens treated with n-HAp alone had higher microhardness values and inhibitory effect on the cariogenic bacteria. Conclusion: Non-Collagenous Protein analogs incorporated in n-HAp could remineralize the demineralised dentin and had antibacterial efficacy against S mutans.